+0  
 
0
95
1
avatar

3, 7*(x-1)-2, 5*(x+2)=x-3, 9

 Apr 22, 2021
 #1
avatar+121003 
+1

3.7 ( x - 1)^2  - 2.5 (x + 2)  =  x - 3.9    simplify

 

3.7  ( x ^2  - 2x  + 1)  - 2.5 (x + 2)  =  x - 3.9

 

3.7x^2  - 7.4x + 3.7  - 2.5x  - 5  =  x - 3.9

 

3.7x^2 - 9.9x  - 1.3  =  x - 3.9

 

3.7x^2  - 10.9x + 2.6  =  0             multiply  through  by 10

 

37x^2  - 109x + 26  =  0

 

Use  the quad formula

 

x  =    109 ±√ (109^2  - 4 (26)(37)

         __________________________

                           2 * 37

 

This  evaluates to     

 

x   ≈  .261       or       x   ≈  2.684

 

 

cool cool cool

 Apr 22, 2021

8 Online Users

avatar